A Brucella spp. protease inhibitor limits antigen lysosomal proteolysis, increases cross-presentation, and enhances CD8+ T Cell responses - Coria, Lorena M. (2016)
In this study, we demonstrate that the unlipidated (U) outer membrane protein (Omp) 19 from Brucella spp. is a competitive inhibitor of human cathepsin L. U-Omp19 inhibits lysosome cathepsins and APC-derived microsome activity in vitro and partially inhibits lysosomal cathepsin L activity within live APCs. Codelivery of U-Omp19 with the Ag can reduce intracellular Ag digestion and increases Ag half-life in dendritic cells (DCs). U-Omp19 retains the Ag in Lamp-2(+) compartments after its internalization and promotes a sustained expression of MHC class I/peptide complexes in the cell surface of DCs. Consequently, U-Omp19 enhances Ag cross-presentation by DCs to CD8(+) T cells. U-Omp19 s.c. delivery induces the recruitment of CD11c(+)CD8α(+) DCs and monocytes to lymph nodes whereas it partially limits in vivo Ag proteolysis inside DCs. Accordingly, this protein is able to induce CD8(+) T cell responses in vivo against codelivered Ag. Antitumor responses were elicited after U-Omp19 coadministration, increasing survival of mice in a murine melanoma challenge model. Collectively, these results indicate that a cysteine protease inhibitor from bacterial origin could be a suitable component of vaccine formulations against tumors.